Characterization of a monoclonal antibody to human erythropoietin. - Weiss, T L (1982)
Hybrid cells that synthesize a monospecific antibody directed toward erythropoietin have been produced by the fusion of mouse plasmacytoma cells with spleen cells from rats immunized against human erythropoietin. The antibody binds the alpha and beta forms and the asialo alpha form of erythropoietin to the same extent. It is an immunoglobulin of the IgG class and binds only erythropoietin in an impure preparation of the hormone. Biologically active unlabeled erythropoietin competes with biologically inactive radiolabeled hormone for monoclonal antibody binding sites. In addition, the biological activity of erythropoietin measured in vitro is not inactivated when it is bound by the monoclonal antibody.